Characteristics and priority control species of ambient VOCs in a coal-coking industrial park in the Fenwei Plain - Yifei Chen; Yi Ning; Jing Ma; Fengxian Liu; Ling Mu; Siyu Liang; Huili Jin; Qian Zhang; Yijie Bi (Environmental Pollution, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Reconstruction and evolution analysis of long-term terrestrial water storage anomalies in Xinjiang based on time series decomposition and multi-model coupling - Zilong Li; Zhenxia Mu; Jing Liu; Xiaoyan Qiu (Journal of Hydrology, 2026)

Land-use change dominates amphibian biodiversity loss, with antagonistic interactions with climate change in the karst region of Guizhou, China - Jing Liu; Shize Li; Gang Wei; Tuo Shen; Lang Mu; Haijun Su (Journal of Environmental Management, 2026)

Rare earth Ce3+/Ce4+ redox effect coupled S-scheme heterojunction synergistically boost electron transfer for efficient photocatalytic environmental remediation - Dongyu Xu; Jiangyu Wang; Pengshuai Yin; Jing Zhang; Situ Mu; Li He; Chun Liu (Environmental Research, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

OcisMILPNet: A Graph-Based MILP Approach for Sparse Operations in Open-Channel Irrigation Networks - Wentao Hou; Haorui Chen; Shaohui Zhang; Jing Fu; Juyan Mu; Boxiong Zhang; Meijian Bai; Yinong Li; Baozhong Zhang (Water Resources Management, 2026)

Unveiling the S-scheme charge transfer in MOF-808/PPy heterojunctions for enhanced Se(IV) photoreduction and subsequent mercury capture - Yu Liang; Xueqing Zhang; Yirui Li; Xiangyu Xiao; Tingmei Ma; Xiao Mu; Jing Zhao; Jiayiwen Wang; Huanhuan Xiao; Jiaxu Zhang (Process Safety and Environmental Protection, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Spatiotemporal activity patterns of urban residents and nonlinear built-environment associations: Evidence from Shanghai using GPS traces and time-use diaries - Jing Guo; De Wang; Longxu Yan; Jing Xia; Lingting Mu; Yinong Liu; Jun Liu; Yuan Li (Applied Geography, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Alterations in the ecological amplitude of summer-dormant submerged macrophyte serve as sensitive indicators for the ecological risk of PFAS in water - Zhenhan Li; Hongwei Yu; Diga Gang; Quanlin Lu; He Ji; Jichun Mu; Xiaoyan Zheng; Jing Qi; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2026)

Polylactic acid microplastics regulate organophosphorus pesticide impacts on phosphorus bioavailability in soil-plant systems - Gaowei Tan; Lingling Ding; Darrell W.S. Tang; Yan Wang; Jing Yang; Hongyu Mu; Xiaomei Yang (Journal of Hazardous Materials, 2026)

Enhanced chlorine photolysis and 1H-benzotriazole degradation in water under the Far-UVC (UV222) irradiation - Jia-Jing Lyu; Qing Bai; Qian-Yuan Wu; Yu-Jia Nong; Mu-Da Han; Min-Yong Lee; Zhong-Quan Ren; Jiang-Lei Xiong; Wen-Long Wang (Journal of Environmental Chemical Engineering, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

The velvet protein CsVeA regulates asexual and sexual development, stress response, and virulence in the rubber anthracnose fungus Colletotrichum siamense - Jing Gao; Min Li; Sheng Li; Qiuyu Mu; Xiaoyu Li; Zhiqiang Liu (Physiological and Molecular Plant Pathology, 2026)

Fluvial evolution model for the paleotropics in the early Triassic hyperthermal period: An example from the Shuiyuguan area in North China - Ya-Nan Shi; Longyi Shao; Christopher R. Fielding; Haojie Lian; Ya-Nan Li; Kai Zhou; Guangyuan Mu; Jing Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Atomically precise Pd4 cluster on monolayer MoS2 for efficient overall water splitting - Yuxin Xu; Jing Ma; Tao Ma; Jiehang Wei; Mengjia Fu; Wenjuan Wang; Shouqin Mu; Xin Wang; Yingtao Liu (Fuel, 2026)

Bisphenol analogs affected hepatic development and disrupted lipid homeostasis in zebrafish larvae - Yao Zheng; Ying Huang; Jiajia Li; Liyan Teng; Yanyang Xu; Lilai Yuan; Wenbo Yang; Jing Qiu; Yongzhong Qian; Tingting Chai; Xiyan Mu (Environmental Pollution, 2026)

The path to breaking the impasse of the marine negative emission economy: An empirical study of the multi-dimensional spillover effects of blue carbon fisheries in Shandong Province - Jing Sun; Huining Liu; Mengfei Li; Hairong Mu; Chenying Cai; Haijuan Wang (Regional Studies in Marine Science, 2026)

Anthropogenic drivers of the composition and distribution of pharmaceuticals and personal care products in landfill leachate in China - Hongxin Mu; Liqun He; Shuai Sun; Shenghu Zhang; Hongqiang Ren; Bing Wu; Houhu Zhang; Yuanqing Bu; Jing Yu (Journal of Environmental Chemical Engineering, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Imaging orientation matters: Challenges in leaf area index measurement on slopes via levelled versus tilted photography - Yongkang Lai; Xihan Mu; Dasheng Fan; Jie Zou; Jing M. Chen; Weihua Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Metabolic coupling of arsenic, carbon, nitrogen, sulfur and iron in high-salinity groundwater in the Yellow River Delta: Insights from metagenomic analyses - Chuanshun Zhi; Dahai Wang; Baonan He; Guohua Hou; Maosheng Gao; Hui Mu; Ruchun Wei; Xiancang Wu; Jing Bai; Yufei Jiao; Xiaonong Hu (Water Research, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Distribution and evolution of distress in embankment-bridge transition sections of the Gonghe–Yushu Expressway in degrading permafrost regions - Bingyan Li; Minghao Liu; Yanhu Mu; Jing Luo; Xin Ju; Fei Yin; Fan Yu; Yunhui Huang (Transportation Geotechnics, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A flexible methanol production process scheduled by carbon price fluctuation: Techno-economic and risk analysis - Jincheng Pan; Jiusheng Mu; Jing Ding; Chundong Zhang; Hui Wan; Guofeng Guan (Journal of Cleaner Production, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

MetaSD: a unified framework for scalable downscaling of meteorological variables in diverse situations - Jing Hu; Honghu Zhang; Peng Zheng; Jialing Mu; Xi Wu; Xiaomeng Huang (Climate Dynamics, 2026)

Study on plasma-activated supersonic water fog atomization and dust suppression performance - Mu Xinsheng; Ge Shaocheng; Zhang Tian; Jing Deji; Liu Shuo; Sun Liying; Pang Xingyu (Process Safety and Environmental Protection, 2026)

Role of flow electrode chamber channel depth in charge transfer and ion migration in FCDI: Mechanistic insights and energy efficiency evaluation - Cheng Wang; Jianrui Niu; Situ Mu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Research progress on exogenous substances and their mechanisms of action in alleviating low-temperature stress in plants - Jiayi Chen; Qian Zhou; Qiong Wu; Jun Yang; Bihui Huang; Wenli Mu; Qinshuang Mei; Heping Zhao; Haifang Hu; Fenglan Liu; Jing Guo; Huixin Zhao (Planta, 2026)

Integrated surface-enhanced Raman spectroscopy and machine learning for identification and quantification of multi-target pesticide residues in fruit juices - Shen Jiang; Qiuyun Li; Xubin Quan; Yaowen Xing; Yujiang Huang; Xuming Mu; Yitong Meng; Guangrun Wu; Tong Ju; Yuhan Chu; Ruiyao Ma; Jing Wu; et al. (Food Chemistry, 2026)

A multifunctional ion-conductive hydrogel with supramolecular interactions for wearable sensing: Human motion monitoring and Morse code communication - Ying Chen; Shenghua Lv; Leipeng Liu; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She (Chemical Engineering Journal, 2026)

Etched MOF-reinforced nanocellulose aerogels with hierarchical porosity for synergistic flame retardancy, thermal insulation, and self-cleaning - Jing Ren; Junfeng Peng; Mengmeng Guo; Jing Li; Zimeng Mu; Chunzu Cheng; Min Gao; Qun Li; Zhiqiang Li (Chemical Engineering Journal, 2026)

Redox electrolyte enhances dual-anode FCDI (DA-FCDI) desalination of brackish and synchronously removal NOM - Kexin Kang; Situ Mu; Jianrui Niu; Yongkun Shi; Jing Zhang; Chun Liu; Junjun Ma (Chemical Engineering Journal, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Demand-driven grafting engineering of IMC/PAM ionic conductive hydrogel: Multifunctional platforms for wearable sensors and TENGs - Ying Chen; Shenghua Lv; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

Water-induced distress characteristics and mechanism of a separated expressway traversing thaw-sensitive permafrost zones - Minghao Liu; Bingyan Li; Yanhu Mu; Jing Luo; Fei Yin; Xiangbing Kong (Cold Regions Science and Technology, 2025)

Single-layer CoMoS anchored on reduced graphene oxide for efficient and stable hydrodeoxygenation of lignin-derived phenolics to arenes - Jing Cao; Peiling Liu; Fangmei Teng; Jialing Liu; Yuting Ni; Xianghui Liu; Jiali Mu; Cen Zhang (Bioresource Technology, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

taVNS alleviates preeclampsia-induced vascular endothelial dysfunction via α7nAChR- IP3R1/GRP75/VDAC1 signal pathway - Jing Zhao; Yuman Lei; Chengcheng Mu; Yuwei Wu; Rourou Fang; Dongdong Wu; Shouzhu Xu; Haifa Qiao (Inflammation Research, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Evaluation of harmful impact of low concentration cylindrospermopsin through zebrafish behavioral endpoints under multiple life stages - Minghui Fu; Yining Zhang; Linjie Luo; Minglu Wu; Liyan Teng; Jiandong Mu; Guohua Xiao; Yanyang Xu; Jing Qiu; Tingting Chai; Yongzhong Qian; Guijie Hao; et al. (Journal of Hazardous Materials, 2025)

Anti-melanogenic effect and mechanism of oxypaeoniflorin derived from edible Paeonia ostii flower on melanogenesis in B16F10 cells and zebrafish - Kejie Peng; Yixuan Wang; Zhangtie Wang; Jing Wang; Yuhang Zhu; Qiannan Pan; Yumeng Li; Jian Mu; Xiuxin Zhang; Baiyi Lu (Food Bioscience, 2025)

Construction of MXene/gelatin foam hydrogel with multi-stage porous for efficient solar-driven interfacial evaporation and ion removal - Jialong She; Shenghua Lv; Tingxiang He; Ying Chen; Yanlu Mu; Jinru Liu; Jing Xu; Xiangyi Liu; Leipeng Liu (Chemical Engineering Journal, 2025)

Mechanistic insights into enhanced volatile pyridine biodegradation through shortcut pyridine-N transformation in counter-diffusion biofilms by regulating biofilm stratification and microbial spatial interactions - Peng Zheng; Yan Li; Youpeng Cheng; Jing Wang; Yixuan Wang; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

High-Precision Small-Scale 3D Seismic Technology for Natural Gas Hydrate Exploration in the Northern South China Sea - Dasen Zhou; Siqing Liu; Xianjun Zeng; Limin Gou; Jing Li; Jingjing Zhang; Xiaozhu Hao; Qingxian Zhao; Qingwang Yao; Jiafa Zhang; Jiaqi Shen; Zelin Mu; et al. (Journal of Marine Science and Engineering, 2025)
To address the demand for high-precision exploration of natural gas hydrates in the northern South China Sea, this paper presents a novel high-precision small-scale 3D seismic exploration technology. The research team independently developed a seismic acquisition system, incorporating innovative designs such as a narrow trace spacing of 3.125 m and a short streamer length of 150 m. By integrating advanced processing techniques, including pre-stack noise suppression, spectral broadening, and refined velocity analysis, the system significantly enhances the precision and spatial resolution of shallow seismic data. During field trials in the Qiongdongnan basin, the system successfully acquired 3D seismic data over an area of 50 km2, enabling fine-scale imaging of sub-seabed strata within the upper 300 m. This represents a notable improvement in resolution compared to conventional 3D seismic technologies. When benchmarked against international counterparts such as P-cable, our system demonstrates distinct advantages in terms of exploration depth (reaching 1800 m) and dominant frequency range (spanning 10~390 Hz). The research findings provide a reliable technical approach for the detailed characterization of natural gas hydrates and the inversion of reservoir parameters, thereby holding significant practical value for advancing the industrial development of natural gas hydrates in China’s offshore areas.

Mining robust in situ phosphorus-accumulating organisms via single-cell RACS-Culture for rational ecosystem engineering - Xiaoyan Jing; Yanhai Gong; Yishang Ren; Liyan Wang; Runzhi Mu; Pengcheng Sun; Zhidian Diao; Yu Meng; Liming Huang; Xixian Wang; Jia Zhang; Jiaxuan Luan; et al. (Water Research, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

A novel phage LTH02 for shiga toxin-producing Escherichia coli: Biological characteristics, whole genomic analysis, and preliminary application in food - Mingwei Ma; Zhenhuan He; Xiaonan Yang; Yinghao He; Leiqian Huang; Chang Liu; Jing Mu; Lei Lei; Gonghe Li; Wende Wu; Min Zheng; Mingxian Shi; et al. (Food Bioscience, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Synergistic microstructure regulation of coal tar pitch based‑carbon by pre-oxidation and iodine treatment for its high-plateau-capacity sodium storage - Yuli Wei; Qing Wang; Qing Liu; Rongzhe Wang; Shaohua Luo; Lixiong Qian; Yahui Zhang; Pengqing Hou; Shengxue Yan; Xin Liu; Jing Guo; Wenning Mu (Chemical Engineering Journal, 2025)

Ni/CeO2 composited hydrogel evaporator for high-light solar-driven evaporation with multi-environmental adaptability - Fengmei He; Xiaojiang Mu; Yulian Chen; Tingting Yang; Xiangyang Li; Yitong Wang; Zhixiang Zhang; Jianhua Zhou; Jing Liu; Xiaoyang Wang; Lei Miao (Journal of Cleaner Production, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

Behavioral, Hematological, Histological, Physiological Regulation and Gene Expression in Response to Heat Stress in Amur Minnow (Phoxinus lagowskii) - Weijie Mu; Jing Wang; Yanyan Zhou; Shibo Feng; Ye Huang; Qianyu Li (Fishes, 2025)
Rising water temperatures due to climate change pose a significant threat to Phoxinus lagowskii, a cold-water fish that is ecologically vital to the high-latitude regions of China. This study assessed heat stress effects on behavioral, hematological, histological, physiological, and molecular responses in P. lagowskii. The critical maximum temperature (CTmax) was determined using the loss of equilibrium (LOE) method, with the CTmax reaching 29 °C. Elevated temperatures lead to an increase in the OBR. Fish were subjected to acute heat stress at 28 °C (below CTmax) for 48 h, with samples collected during the 48 h period. RBC, WBC, HGB, and HCT significantly increased during heat stress but decreased 12 h after heat stress. The levels of serum cortisol and blood glucose after heat stress were significantly higher than those in the control group. After heat stress, the height of the ILCM in the gills increased significantly, and the liver exhibited vacuolar degeneration and hypopigmentation. The activities of Na+-K+-ATPase and Ca2+-Mg2+-ATPase in the gills initially increased and then decreased over the duration of heat stress. Most enzyme activities (PK, LDH, PFK, and HK) decreased during heat stress, while LPL and HL levels increased, indicating that lipid metabolism was the primary utilization process under heat stress. There was an increase in SOD activity at 12 h, followed by a decrease at 24 h, and an increase in CAT activity under heat stress. Integrated biomarker response (IBR) and principal component analysis (PCA) were employed to synthesize multi-level responses. The IBR values reached their peak at 3 h and 48 h of heat stress. We observed an upregulation of heat shock proteins (Hsp70, Hsp90, and Hsc70) as well as interleukin-10 (IL-10) in response to heat stress. Our findings offer novel insights into the mechanisms underlying the heat stress response in P. lagowskii, thereby enhancing our understanding of the effects of heat stress on cold-water fish.

MiR-30d-5p Modulates Glucose and Lipid Metabolism by Targeting CD73 through the AMPK Pathway - Mingjie Song; Juan Wang; Wenli Mu; Yanwei Zheng; Yanjun Cai; Jing Liu; Yu Xia (Cell Biochemistry and Biophysics, 2025)

Gradient purification of surface water and ultrafiltration membrane fouling mitigation based on Fe(VI) multifunctional integration characteristics: Is a sedimentation unit necessary? - Kunyu Chen; Jie Wang; Xiaojiang Huang; Ruimin Mu; Congwei Luo; Daoji Wu; Jing Liu; Jinsuo Lu; Xiaoxiang Cheng (Water Research, 2025)

Enhancing carbon neutrality through blue carbon fisheries: Spatial analysis in Shandong - Jing Sun; Mengfei Li; Ningning Zhai; Hairong Mu; Weixiao Li; Huining Liu (Regional Studies in Marine Science, 2025)

An Investigation Into the Long‐Chain Propagation Patterns and Driving Factors of Multiple Types of Droughts in Xinjiang - Shikang Zhao; Zhenxia Mu; Zilong Li; Xiaoyan Qiu; Jing Liu (International Journal of Climatology, 2025)
The process of drought propagation is extremely complex and involves all aspects of the water cycle. Clarifying the mechanism of drought propagation is of great significance for understanding the evolutionary pattern of drought and constructing a drought early warning system. However, due to the complexity of droughts and the numerous factors influencing them, there are certain limitations and shortcomings in studying the intrinsic links, propagation characteristics and triggering mechanisms of multiple drought types. To this end, this paper takes the Xinjiang region as the research object, identifies the drought events based on the run theory and determines the drought propagation time by matching the drought events; risk probabilities, trigger thresholds and drivers between different drought types were explored using copula functions, Bayesian theory and random forest models. The results show that (1) the average drought propagation time from meteorology to agriculture and from meteorology to hydrology in Xinjiang is 2.1 and 2.8 months, respectively. (2) The probability of the occurrence of agricultural (hydrological) drought increased with the severity of meteorological (agricultural) droughts. Specifically, the average probability of extreme meteorological (agricultural) droughts triggering mild agricultural (hydrological) droughts reached 89% (41%), with an average trigger threshold of −1 (−2.2). (3) Mild meteorological drought on the northern slopes of the Tianshan mountains was the primary trigger for mild agricultural drought, with an average trigger probability and threshold of 45% and −0.89, respectively. In contrast, moderate meteorological drought on the southern slopes of the Tianshan mountains was the main trigger for mild agricultural drought, with an average trigger probability and threshold of 56% and −1.1, respectively. (4) Meteorological drought triggers a significant reduction in the threshold for agricultural drought, mainly influenced by precipitation and potential evapotranspiration. Agricultural drought triggers a significant reduction in the threshold for hydrological drought, with temperature and potential evapotranspiration being the main drivers of the threshold change.

Bacterial and archaeal community successions in high-salinity groundwater and their potential impact on arsenic cycling - Chuanshun Zhi; Xiaonong Hu; Zhuo Zhang; Baonan He; Jing Bai; Xiancang Wu; Hui Mu; Wenbo Chang; Fan Yang; Qi Qiu; Yuzheng Wang (Journal of Hydrology, 2025)

Mechanistic insights into substituent-induced hydrolytic debromination and electron flow of bromophenols under nitrate-reducing conditions - Yunhao Xu; Jing Wang; Qiang Chi; Peng Zheng; Hanjuan Lv; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

A robust CMCNa-PAM salt-inhibiting double-network hydrogel for efficient solar interfacial evaporation - Junzhe Huang; Jianhua Zhou; Yang Long; Xiaojiang Mu; Zhixiang Zhang; Yanqing Zhu; Gang Xu; Jing Liu; Jun-Liang Chen; Lei Miao (Journal of Environmental Chemical Engineering, 2025)

Novel insights into the evolution of dissolved organic matter during different full-scale advanced treatment processes for textile secondary effluent - Cheng Cheng; Chuanyang Liu; Jian Shen; Siting Wang; Xiaojin Wu; Qiuran Xiong; Hongmei Mu; Bingliang Zhang; Jing Wu (Journal of Environmental Chemical Engineering, 2025)

Characterization of the sensory evaluation system for fermented chili pepper (Capsicum annuum L.) using GC-O-MS and sensory analysis techniques - Zhonghui Mu; Yuzhang Zhu; Li Ran; Cen Li; Jing Jin; Lincheng Zhang; Shuoqiu Tong; Yongjun Wu (International Journal of Gastronomy and Food Science, 2025)

Effects of tourmaline on anaerobic ammonia oxidation process: Mechanistic Understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Shan Qiu; Baojian Jing; Shuoqi Ren; Jue Wang; Mengxuan Deng; Mengqi Fu; Zhongqi Jiang; Fengxia Deng; Jinghui Wang; Jie Qiu (Chemical Engineering Journal, 2025)

A Review on Development, Challenges, and Future Perspectives of Ensemble Forecast - Jing Chen; Yuejian Zhu; Wansuo Duan; Xiefei Zhi; Jinzhong Min; Xiaoli Li; Guo Deng; Huiling Yuan; Jie Feng; Jun Du; Qiaoping Li; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

Mild cognitive impairment is associated with effect of uremic metabolites on gray matter structural changes in end-stage kidney disease - Huijie Yuan; Zhaoyao Luo; Jing Yang; Shaohui Ma; Peng Li; Xinyi Wang; Hang Su; Ronghua He; Junya Mu; Yuchen Zhang (Brain Imaging and Behavior, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Tree-ring width series of synchronously growing trees' classes effectively optimizes their climatic signal - Jing Yang; Ouya Fang; Hengfeng Jia; Jiacheng Zheng; Yumei Mu; Paolo Cherubini (Agricultural and Forest Meteorology, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Intelligent veins recognition method for slope rock mass geological images in complex background noise - Niu Wen-jing; Chen Yuan-xin; He Ben-guo; Chen Guang-mu; Qiu Zhen-hua; Fan Wen-yu (Computers & Geosciences, 2025)

Deciphering the key role of biofilm and mechanisms in high-strength nitrogen removal within the anammox coupled partial S0-driven autotrophic denitrification system - Shuyan Yin; Yi-Xuan Wang; Cheng Hou; Jing Wang; Jing Xu; Xinbai Jiang; Dan Chen; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

TUBB4A Inhibits Glioma Development by Regulating ROS-PINK1/Parkin-Mitophagy Pathway - Xueru Xi; Suqin Chen; Xiaoli Zhao; Zimu Zhou; Shanjie Zhu; Xurui Ren; Xiaomei Wang; Jing Wu; Shuai Mu; Xianwen Li; Enfang Shan; Yan Cui (Molecular Neurobiology, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Integrated metabolome and transcriptome analysis provides insights into the mechanisms of terpenoid biosynthesis in tea plants (Camellia sinensis) - Junchi Wei; Xingyu Mu; Shaoying Wang; Qi Wei; Luqin Zhu; Xiangna Zhang; Jing Zhang; Xiaobo Liu; Beibei Wen; Meifeng Li; Jianjun Liu (Food Research International, 2025)

A novel aptasensor integrating the DNA rolling nanomachine and Tb/COF/KB as dual signal amplifiers for kanamycin detection in foods - Yujie Chen; Zhaode Mu; Jianli Zuo; Min Qing; Jing Zhou; Lijuan Bai (Food Chemistry, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

USP9X deubiquitinates TRRAP to promote glioblastoma cell proliferation and migration and M2 macrophage polarization - Bin Mu; Jiangpeng Jing; Ruichun Li; Chuankun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unsupervised Meteorological Downscaling Based on Dual Learning and Subgrid-scale Auxiliary Information - Jing Hu; Jialing Mu; Xiaomeng Huang; Xi Wu (Advances in Atmospheric Sciences, 2025)

Net primary productivity of paleo-peatlands linked to deep-time glacial periods in the late Carboniferous and early Permian icehouse interval - Yanwen Shao; Fenghua Zhao; Baruch Spiro; Dehui Li; Guangyuan Mu; Jiangman Chu; Jing Lu; Longyi Shao (International Journal of Coal Geology, 2024)

In vitro fermentation of V-type starch inclusion complexes: The controlled release of ferulic acid and beneficial modulation of the gut microbiota - Shiyi Lu; Gengjie Cui; Yifan Mu; Kaige Li; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Bioscience, 2024)

Evaluating and enhancing the applicability of thermal comfort indices in diverse outdoor environments using Bayesian and random forest regression - Wenqiang Jing; Jiayan Liu; Zeming Qin; Teng Mu; Zhemin Ge; Yuting Dong (Energy and Buildings, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

β-arrestin2 promotes angiogenesis of liver sinusoidal endothelial cells through the VEGF/VEGFR2 pathway to aggravate cirrhosis - Feng Gao; Wei Mu; Jiangbo Fan; Jing Shen (Toxicology Letters, 2024)

Multi-stimulus response AIE fluorescent hydrogel for “Blind box” multistage secure information encryption - Jing Liu; Shasha Yang; Qi Liu; Jie Wang; Yongchang Mu; Yingchun Li; Jie Li (Chemical Engineering Journal, 2024)

Effects of tourmaline on the establishment, idling, and recovery of partial nitrification: Mechanistic understanding and performance evaluation - Mu Yuan; Xiaohan Jiang; Baojian Jing; Jue Wang; Mengqi Fu; Mengxuan Deng; Shuoqi Ren; Zhongqi Jiang; Fengxia Deng; Shan Qiu (Chemical Engineering Journal, 2024)

Seasonal simulation and source apportionment of SO42− with integration of major highlighted chemical pathways in WRF-Chem model in the NCP - Xiaoxi Zhao; Xiujuan Zhao; Dan Chen; Jing Xu; Yujing Mu; Bo Hu (Atmospheric Pollution Research, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Influences of reformate on the performance of high temperature proton exchange membrane fuel cell and its optimization strategy - Mu Sun; Jicai Huang; Zhangxun Xia; Congrong Yang; Fenning Jing; Suli Wang; Gongquan Sun (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Experimental Study on Mechanical Behavior, Fracture Characteristics, and Acoustic Emission Damage Characteristics of Sandstone Under Triaxial Multistage Stress Disturbance - Sheng-Qi Yang; Jing Yang; Zong-Long Mu; Guang-Jian Liu; Man Huang; Ke-Sheng Li; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Research on Influencing Factors of Cable Clamp Bolt Elastic Interaction in Cross-Ocean Suspension Bridges - Fengrui Mu; Bo Wang; Yongjun Zhou; Yuan Jing; Yu Zhao; Zhiran Luo (Journal of Marine Science and Engineering, 2024)
Suspension bridges are the most common type of bridge used to cross the ocean. The cable clamps in suspension bridges clamp the main cables by bolt preload, but the elastic interaction of the bolts reduces the preload, which is detrimental to the force in suspension bridges. However, research on the factors influencing the elastic interaction of cable clamp bolts in suspension bridges is currently limited. This paper aims to explore the law of influence of external factors on the elastic interaction of bolts through a combined approach of theoretical analysis, full-scale experiment, and finite element simulation. The results indicate that the average preload loss was reduced by about 27% when the elastic modulus was increased by about 110%. The average preload loss was reduced by about 45% when the bolt center distance was increased by 75%. The number of bolts has a small effect on the elastic interaction, which can be ignored. When the preload of bolt installation was increased by 133%, the average preload loss was reduced by approximately 125%, which was almost a linear relationship. Tightening the bolt from the center bolt creates greater elastic interaction. The conclusions can provide suggestions for reducing the elastic interaction of bolts in the design and construction of suspension bridge cable clamps.

Ammonia monooxygenase-mediated cometabolic biotransformation of volatile 4-chlorophenol in nitrifying counter-diffused biofilms: A combined molecular dynamics simulation, DFT calculation and experimental study - Peng Zheng; Wenqiang Li; Yan Li; Youpeng Cheng; Jing Wang; Yang Mu; Jinyou Shen (Water Research, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Water quality constraints H2O2 production in a dual-fiber photocatalytic reactor - Jing Wang; Yen-Jung Sean Lai; Tzu-Heng Wang; Chao Zeng; Paul Westerhoff; Yang Mu (Water Research, 2024)

Multidimensional occurrence and diet risk of emerging contaminants in freshwater with urban agglomerations - Tingting Chai; Yinyin Jin; Feng Cui; Zongjie Li; Mingxiao Li; Shunlong Meng; Lilai Yuan; Jing Qiu; Jiandong Mu; Guohua Xiao; Xiyan Mu; Yongzhong Qian (Journal of Hazardous Materials, 2024)

Bio-fuel production from hydroconversion of hexadecane over Pt/SAPO-11 catalysts - Chao Mu; Junhao Sun; Chen Xie; Jing Xu; Jinxuan Bao; Haozhe Zhang; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2024)

Akkermansia muciniphila Protects Against Antibiotic-Associated Diarrhea in Mice - Shenyin Liu; Suying Zhao; Zhiwei Cheng; Yilin Ren; Xinyi Shi; Jing Mu; Xiangyang Ge; Yuan Dai; Lei Li; Zhan Zhang (Probiotics and Antimicrobial Proteins, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Marinobacter sediminicola sp. nov. and Marinobacter xiaoshiensis sp. nov., Isolated from Coastal Sediment - Jing An; Run-Yuan Mao; Shu-Xin Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Current Microbiology, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Ecosystem health assessment: a PSR analysis combining AHP and EW methods for Sansha Bay, China - Yue Li; Yaling Huang; Xiaoyun Zhang; Yawen Jiang; Xiaoshan Jing; Yihong Deng; Rongmao Li; Degang Jiang; Jingli Mu (Frontiers in Marine Science, 2024)
Maintaining the health of coastal aquaculture ecosystems is crucial for sustainable development. Therefore, establishing a specific ecosystem health assessment index system for aquaculture bays is paramount. This system allows for the evaluation of the health status of these bays and aids in the planning and restoration of fishery habitats. Utilizing the well-known “Pressure-State-Response” framework, a comprehensive evaluation index system with 14 indicators was developed. Additionally, the analytic hierarchy process and entropy weight methods were employed to assess the ecosystem health of Sansha Bay, a representative aquaculture bay in Fujian Province, China. The results revealed variations in health status across four zones in 2020, categorized as “good” or “excellent”. However, the security index was more spatially distributed and classified from “fair” to “safety”. Key indicators critical to sustaining the health of the aquaculture bay ecosystem included the regional environmental risk index, the proportion of industrial discharge outlets, the zooplankton species diversity index, the phytoplankton species diversity index, the molar ratio of phosphorus to nitrogen, and the size of nature reserves. According to the assessments of ecosystem health and ecological security, vigorous endeavors in aquatic ecology are paramount to ensure the enduring sustainability of aquaculture, with a specific emphasis on Zoning 1 and Zoning 4. These findings not only enhance and expand the methods for assessing the health of aquaculture bay ecosystems but also provide a scientific basis for the conservation of fishery habitats and the green, high-quality development of the aquaculture industry in Sansha Bay.

Synergistic developmental effects of zebrafish exposed to combined perfluorooctanoic acid and atrazine - Xiaoyu Zhao; Beinan Wang; Xiao Song; Linjuan He; Wei Zhang; Yongzhong Qian; Xiyan Mu; Jing Qiu (Chemosphere, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Degradation of the chiral fungicide penthiopyrad by six bacteria strains isolated from soils and the potential stereoselectivity - Jinming Chang; Li Dou; Shiyin Mu; Du Chi; Jing Shi; Kankan Zhang (Journal of Environmental Chemical Engineering, 2024)

Sediment provenance variations driven by sea level in the eastern Arabian Sea since the MIS 9 period: Evidence from geochemical proxies - Tongbing Fang; Shengfa Liu; Kaikai Wu; Hui Zhang; Peng Cao; Mu Huang; Lina Ai; Wenjing Qi; Jing Tao; Xuefa Shi (Journal of Asian Earth Sciences, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Assessing shorebird mortalities due to razor clam aquaculture at key migratory stopover sites in southeastern China - Dan Liang; Tong Mu; Ziyou Yang; Xingli Giam; Yudi Wang; Jing Li; Shangxiao Cai; Xuelian Zhang; Yixiao Wang; Yang Liu; David S. Wilcove (Conservation Biology, 2024)
Aquaculture can provide foraging habitat for birds, but it can also result in intentional and accidental mortality. We examined an overlooked conflict between razor clam ( Sinonovacula spp.) aquaculture and declining shorebirds in southeastern China's Fujian and Zhejiang provinces. We surveyed 6 out of 11 internationally important stopover sites for these shorebirds and monitored shorebird mortality in 2 sites (Xinghua Bay, Yueqing Bay) with razor clam aquaculture. We visited an additional 32 sites in these 2 provinces to determine if there was netting in other razor clam farms. Approximately 8–9 km 2 of intertidal foraging habitat was covered by horizontal nets to prevent birds from feeding on young razor clams at Xinghua Bay and Yueqing Bay. We conservatively estimated that 13,676 (2.5th–97.5th percentile 8,330–21,285) individual shorebirds were entangled in the nets at the 2 monitored sites in April and May 2021, including 2 endangered and 7 near‐threatened species. Mortality of 5 species for which we had sufficient data accounted for 0.76% (black‐tailed godwit [ Limosa limosa ]) to 4.27% (terek sandpiper [ Xenus cinereus ]) of their total flyway populations. This level of mortality could strongly affect their populations. We found netting at 17 additional razor clam farms, indicating a widespread threat to shorebirds. Although razor clams are typically harvested in late March to early April, nets are left on the mudflats throughout the spring and summer, including when the bulk of shorebird migration takes place. Immediately removing these nets after the clam harvest could prevent most of the spring mortality of shorebirds, although this is unlikely to happen without government regulations or economic incentives. To better assess and mitigate the impacts of this conflict, future research should quantify shorebird mortality at other razor clam farms, including during winter, explore less harmful deterrence methods, and assess the socioeconomic factors driving the conflict.

Source apportionment and predictable driving factors contribute to antibiotics profiles in Changshou Lake of the Three Gorges Reservoir area, China - Yue Mu; Bobin Tang; Xian Cheng; Yuanhang Fu; Weibin Huang; Jing Wang; Dewang Ming; Liangshu Xing; Jinzhong Zhang (Journal of Hazardous Materials, 2024)

Monitoring longitudinal antimicrobial resistance trends of Staphylococcus aureus strains worldwide over the past 100 years to decipher its evolution and transmission - Guan-Yu Fang; Feng-Hua Wu; Xiao-Jing Mu; Yu-Jian Jiang; Xing-Quan Liu (Journal of Hazardous Materials, 2024)

A novel sandwich-type electrochemical immunosensor for sensitive detection of zearalenone using NG/PDDA/HNTs and Ti-MOF-KB composites for signal amplification - Xiaodan Jiang; Zhaode Mu; Jie Wang; Jing Zhou; Lijuan Bai (Food Chemistry, 2024)

Contrasting characteristics of continental and oceanic deep convective systems at different life stages from CloudSat observations - Jinming Ge; Xiaoyu Hu; Qingyu Mu; Bochun Liu; Zeen Zhu; Jiajing Du; Jing Su; Qinghao Li; Chi Zhang (Atmospheric Research, 2024)

Horizontal gene transfer in activated sludge enhances microbial antimicrobial resistance and virulence - Guan-Yu Fang; Xing-Quan Liu; Yu-Jian Jiang; Xiao-Jing Mu; Bing-Wen Huang (Science of The Total Environment, 2024)

Assessment of urban resilience and subsystem coupling coordination in the Beijing-Tianjin-Hebei urban agglomeration - Jing Sun; Ningning Zhai; Hairong Mu; Jichao Miao; Weixiao Li; Mengfei Li (Sustainable Cities and Society, 2024)

Atomic force microscopy-based nanoscale infrared techniques for liquid environments - Jian Li; Jing Liang; Mu-Hao Lan; Xing-Hua Xia (Science Bulletin, 2024)

Comprehensive understanding on sources of high levels of fine particulate nitro-aromatic compounds at a coastal rural area in northern China - Yueru Jiang; Xinfeng Wang; Min Li; Yiheng Liang; Zhiyi Liu; Jing Chen; Tianyi Guan; Jiangshan Mu; Yujiao Zhu; He Meng; Yang Zhou; Lan Yao; et al. (Journal of Environmental Sciences, 2024)

The infrastructure cost of permafrost degradation for the Northern Hemisphere - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yuan Huang; Lei Guo; Jing Luo; Guoan Yin; Guohui Zhao; Cuicui Mu (Global Environmental Change, 2024)

Aggregation-induced enhancement of pyrene-based metal-organic framework as a new electrochemiluminescence emitter for ultrasensitive detection of sulfadimethoxine - Junjie Liu; Zhaode Mu; Jing Zhou; Min Qing; Lijuan Bai (Food Chemistry, 2024)

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Starch/carboxymethyl cellulose-based photodynamic packaging material delays the quality deterioration of snap beans via ROS metabolism regulation - Dezhuang Gong; Xinhua Zhang; Jing Zhang; Jingyi Mu; Xiaofeng Han; Xiuling Zhang; Wentao Zhang (Postharvest Biology and Technology, 2023)

A comparative metabolomics study of polyphenols in highland barley (Hordeum vulgare L.) grains with different colors - Yang Yang; Bei Fan; Yuwen Mu; Yang Li; Litao Tong; Lili Wang; Liya Liu; Minmin Li; Peipei Sun; Jing Sun; Fengzhong Wang (Food Research International, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

Groundwater Quality Assessment Using EWQI With Updated Water Quality Classification Criteria: A Case Study in and Around Zhouzhi County, Guanzhong Basin (China) - Yongqiang Yang; Peiyue Li; Vetrimurugan Elumalai; Jing Ning; Fei Xu; Dawei Mu (Exposure and Health, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

Distinct increase in antimicrobial resistance genes among Vibrio parahaemolyticus in recent decades worldwide - Guan-Yu Fang; Xing-Quan Liu; Xiao-Jing Mu; Bing-Wen Huang; Yu-Jian Jiang (Chemosphere, 2023)

The neurobehavioral impacts of typical antibiotics toward zebrafish larvae - Yining Zhang; Xue Li; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Guijie Hao; Xueping Ye; Shunlong Meng; Guohua Xiao; Jiandong Mu; Xiyan Mu; Jing Qiu; et al. (Chemosphere, 2023)

Bisphenol analogues induced social defects and neural impairment in zebrafish - Xiyan Mu; Zaiteng Liu; Xiaoyu Zhao; Lu Chen; Qi Jia; Chengju Wang; Tiejun Li; Yuanming Guo; Jing Qiu; Yongzhong Qian (Science of The Total Environment, 2023)

Rapid identification of hazardous heavy metal-containing waste by combining EDXRF with machine learning: Taking zinc smelting waste as an example - Jing Teng; Yao Shi; Zuo-Hua Liu; Hui-Quan Li; Ming-Xing He; Zhi-Hong Li; Chen-Mu Zhang (Resources, Conservation and Recycling, 2023)

Enhanced biological phosphorus removal by high concentration powder carrier bio-fluidized bed (HPB): Phosphorus distribution, cyclone separation, and metagenomics - Yanyu Mu; Li Wan; Zixuan Liang; Donghai Yang; Hongbo Han; Jing Yi; Xiaohu Dai (Chemosphere, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Endoplasmic reticulum stress: a vital process and potential therapeutic target in chronic obstructive pulmonary disease - Hao Peng; Qing Zhou; Jing Liu; Yi Wang; Ketao Mu; Lei Zhang (Inflammation Research, 2023)

New insights into enhanced biodegradation of 4-bromphenol in a nitrate-reducing system: Process performance and mechanism - Jing Wang; Qiang Chi; Ling Pan; Ranran Zhang; Yang Mu; Jinyou Shen (Water Research, 2023)

Maximizing jet fuel production from n-hexadecane hydrocracking over Pt-supported Y catalysts: Importance of ideal hydrocracking characteristics - Yi Li; Chao Mu; Guangxin Chu; Yule Wang; Jing Xu; Xuan Guo; Yujun Zhao; Shengping Wang; Xinbin Ma (Fuel, 2023)

Aspirin alleviates cisplatin-induced acute kidney injury through the AMPK-PGC-1α signaling pathway - Danning Tong; Enshuang Xu; Ruidong Ge; Mengxin Hu; Shengzi Jin; Jing Mu; Yun Liu (Chemico-Biological Interactions, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Interactions and quantification of multiple influencing factors on cadmium accumulation in soil-rice systems at a large region - Yue Mu; Jingxin Cui; Andi Liu; Shuai Wang; Qiujun Shi; Jing Wang; Shiqiang Wei; Jinzhong Zhang (Science of The Total Environment, 2023)

An enzymatic activity regulation-based clusterzyme sensor array for high-throughput identification of heavy metal ions - Yueyuan Li; Zhaode Mu; Yonghua Yuan; Jing Zhou; Lijuan Bai; Min Qing (Journal of Hazardous Materials, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Volcanism and wildfire associated with deep-time deglaciation during the Artinskian (early Permian) - Ye Wang; Jing Lu; Minfang Yang; Joyce A. Yager; Sarah E. Greene; Ruoyu Sun; Xiaomiao Mu; Xiao Bian; Peixin Zhang; Longyi Shao; Jason Hilton (Global and Planetary Change, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Sequence-paleogeography and coal accumulation of the Late Carboniferous – Early Permian paralic successions in western Shandong Province, northern China - Yanwen Shao; Fenghua Zhao; Guangyuan Mu; Bin Sun; Kaihua Liang; Dongdong Wang; Jing Lu; Shimin Ma; Longyi Shao (Marine and Petroleum Geology, 2023)

Vivianite-induced peroxymonosulfate activation for containment removal under dark conditions: Performance, mechanism and regeneration - Qi Li; Mingzhou Wang; Jia-Qi Chen; Xiaomeng Liu; Jing Wang; Yang Mu (Water Research, 2023)

Insights on the isolation, identification, and degradation characteristics of three bacterial strains against mandipropamid and their application potential for polluted soil remediation - Shiyin Mu; Li Dou; Yu Ye; Hao Zhang; Jing Shi; Kankan Zhang (Pesticide Biochemistry and Physiology, 2023)

Applicability analysis of thermosyphon for thermally stabilizing pipeline foundation permafrost and its layout optimization - Fei Wang; Guoyu Li; Fedorov Alexander; Wei Ma; Dun Chen; Gang Wu; Yanhu Mu; Xinbin Wang; Hongyuan Jing; Zhenrong Zhang (Cold Regions Science and Technology, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Bifunctional electrocatalyst junction engineering: CoP nanoparticles in-situ anchored on Co3(Si2O5)2(OH)2 nanosheets for highly efficient water splitting - Yang Mu; Yifu Zhang; Ziyi Feng; Xueying Dong; Xuyang Jing; Xiaoyu Pei; Yunfeng Zhao; Zongkui Kou; Changgong Meng (Chemical Engineering Journal, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

How do heterogeneous environmental regulations affect the sustainable development of marine green economy? Empirical evidence from China's coastal areas - Jing Sun; Ningning Zhai; Jichao Miao; Hairong Mu; Weixiao Li (Ocean & Coastal Management, 2023)

The chemical index of alteration in Permo-Carboniferous strata in North China as an indicator of environmental and climate change throughout the late Paleozoic Ice Age - Yanan Li; Longyi Shao; Christopher R. Fielding; Tracy D. Frank; Dewei Wang; Guangyuan Mu; Jing Lu (Global and Planetary Change, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

Cryobacterium zhongshanensis sp. nov., an actinobacterium isolated from Antarctic soil - Guojiang Niu; Wenjing Wang; Hongmei Mu; Peiqiang Jiang; Xingtao Ren; Jing Li (Archives of Microbiology, 2023)

Fungal biodiversity and interaction complexity were the important drivers of multifunctionality for flavor production in a spontaneously fermented vinegar - Guan-Yu Fang; Xiao-Jing Mu; Bing-Wen Huang; Guang-Zhong Wu; Yu-Jian Jiang (Innovative Food Science & Emerging Technologies, 2023)

The textural properties of cooked convenience rice upon repeated freeze–thaw treatments are largely affected by water mobility at grain level - Shiyi Lu; Jie Li; Minghao Xu; Yifan Mu; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Recognizing and managing construction land reduction barriers for sustainable land use in China - Jia-He Zhou; Yu-Ming Zhu; Lei He; Hao-Jing Song; Bing-Xu Mu; Fen Lyu (Environment, Development and Sustainability, 2022)

Astrocyte-derived lactate/NADH alters methamphetamine-induced memory consolidation and retrieval by regulating neuronal synaptic plasticity in the dorsal hippocampus - Xu Tan; Xiaoyu Liu; E Liu; Min Liu; Shouhong Mu; Zhaofang Hang; Weikai Han; Tingting Wang; Yang Zhang; Jing Zhang; Qingwei Yue; Jinhao Sun (Brain Structure and Function, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Robiginitalea marina sp. nov., isolated from coastal sediment - Xiao-Qi Xuan; Run-Yuan Mao; Wen-Xing Yu; Jing An; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

A Nonlinear Representation of Model Uncertainty in a Convective-Scale Ensemble Prediction System - Zhizhen Xu; Jing Chen; Mu Mu; Guokun Dai; Yanan Ma (Advances in Atmospheric Sciences, 2022)

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Correction to: Molecular characterization, expression following cold stress, and functional characterization of YB-1 gene in the spotted sea bass (Lateolabrax maculatus) - Zhen Wang; Jing Wang; Weijie Mu; Liqun Liang (Aquaculture International, 2022)

Molecular characterization, expression following cold stress, and functional characterization of YB-1 gene in the spotted sea bass (Lateolabrax maculatus) - Zhen Wang; Jing Wang; Weijie Mu; Liqun Liang (Aquaculture International, 2022)

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

Molecular cloning, characterization and expression analysis of P53 from high latitude fish Phoxinus lagowskii and its response to hypoxia - Jing Wang; Xi Chen; Xinrui Ge; Zhen Wang; Weijie Mu (Fish Physiology and Biochemistry, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Membrane lipid phosphorus reusing and antioxidant protecting played key roles in wild soybean resistance to phosphorus deficiency compared with cultivated soybean - Jing Chen; Ji Zhou; Mingxia Li; Mu Li; Yunan Hu; Tao Zhang; Lianxuan Shi (Plant and Soil, 2022)

First report of plum bark necrosis stem pitting-associated virus affecting sweet cherry in Yunnan, China - Miao Guo; Jing Zhong; Chaowen Wang; Yue Chen; Zhengsong Yang; Tingting Li; Yongbin Wu; Yongqing Mu; Ming Ding; Jiawei He (Journal of Plant Pathology, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Preparation and Evaluation of Novel Supersaturated Solid Dispersion of Magnolol - Jing Zhao; Pan Gao; Chengqiao Mu; Jingqi Ning; Wenbin Deng; Dongxu Ji; Haowei Sun; Xiangrong Zhang; Xinggang Yang (AAPS PharmSciTech, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Frequent central Pacific La Niña events may accelerate Arctic warming since the 1980s - Jing Li; Lin Mu; Linhao Zhong (Acta Oceanologica Sinica, 2021)

Histopathological, hematological, and biochemical changes in high-latitude fish Phoxinus lagowskii exposed to hypoxia - Yuting Yang; Zhen Wang; Jing Wang; Fengming Lyu; Kexin Xu; Weijie Mu (Fish Physiology and Biochemistry, 2021)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Role of Wnt signaling pathways in type 2 diabetes mellitus - Jing Chen; Chong Ning; Jingjing Mu; Dongnan Li; Yan Ma; Xianjun Meng (Molecular and Cellular Biochemistry, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Exosomal miR-21-5p contributes to ovarian cancer progression by regulating CDK6 - Jian Cao; Yuan Zhang; Juan Mu; Dazhen Yang; Xiaoyan Gu; Jing Zhang (Human Cell, 2021)

Correction to: A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

NO oxidation performance and kinetics analysis of BaMO3 (M=Mn, Co) perovskite catalysts - Ran Ao; Liping Ma; Zhiying Guo; Jing Yang; Liusen Mu; Jie Yang; Yi Wei (Environmental Science and Pollution Research, 2021)

Distinct tropical Pacific sea surface temperature anomaly regimes enhanced under recent global warming - Jing Li; Lin Mu; Linhao Zhong (International Journal of Climatology, 2021)
El Niño and Southern Oscillation (ENSO) events are usually monitored by tropical Pacific sea surface temperature anomaly (SSTA) patterns with dramatic impacts on the global climate. To explore the diversity of the tropical Pacific SSTA, a novel method combined empirical orthogonal function analysis and the K‐means clustering algorithm is carried out to classify SSTA patterns during 1950–2016. Meanwhile, the total distance variance and total silhouette value are introduced to determine an optimal number of distinguishable representative SSTA patterns. Ten SSTA patterns are obtained, which shows frequent basin‐wide warming and extreme cold ENSO events in recent decades. It may be attributed to the changes in composition of the intrinsic modes along with the background mode of slowly increasing east–west SST gradient. The comparative analysis between periods 1950–1969 and 1997–2016 suggests that the two regimes of tropical Pacific SSTA, featured as extreme warm and moderate warm/extreme cold patterns respectively, become more distinct under recent global warming.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Sources of particulate organic matter in the Chukchi and Siberian shelves: clues from carbon and nitrogen isotopes - Renming Jia; Xinyue Mu; Min Chen; Jing Zhu; Bo Wang; Xiaopeng Li; A. S. Astakhov; Minfang Zheng; Yusheng Qiu (Acta Oceanologica Sinica, 2020)

A new indole alkaloid with anti-inflammatory from the branches of Nauclea officinalis - Le-Ling Song; Yan-Ling Mu; Hao-Chao Zhang; Gui-Ying Wu; Jing-Yong Sun (Natural Product Research, 2020)

MiRNA-211 triggers an autophagy-dependent apoptosis in cervical cancer cells: regulation of Bcl-2 - Shang Liu; Hongyan Wang; Jing Mu; Hao Wang; Yan Peng; Qi Li; Dongwei Mao; Liyuan Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Influence of CaO-activated silicon-based slag amendment on the growth and heavy metal uptake of vetiver grass (Vetiveria zizanioides) grown in multi-metal-contaminated soils - Jing Mu; Zhengyi Hu; Zijian Xie; Lijuan Huang; Peter E. Holm (Environmental Science and Pollution Research, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Experimental investigation on the optical remote sensing images of internal solitary waves with a smooth surface - Yuan Mei; Jing Wang; Songsong Huang; Haidi Mu; Xu Chen (Acta Oceanologica Sinica, 2019)

Influence of alkaline silicon-based amendment and incorporated with biochar on the growth and heavy metal translocation and accumulation of vetiver grass (Vetiveria zizanioides) grown in multi-metal-contaminated soils - Jing Mu; Zhengyi Hu; Lijuan Huang; Sichen Tang; Peter E. Holm (Journal of Soils and Sediments, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Tepidicella baoligensis sp. nov., A Novel Member of Betaproteobacterium Isolated from an Oil Reservoir - Jing You; Yongbin Li; Shan Hong; Jing Wang; Jiliang Yu; Bozhong Mu; Xiaochen Ma; Yanfen Xue (Current Microbiology, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

Coralloluteibacterium thermophilus sp. nov., A Gammaproteobacterium Isolated from an Oil Reservoir - Jing You; Shan Hong; Jiliang Yu; Lisha Duan; Bo Liu; Bozhong Mu; Cheng Zhou; Yanfen Xue (Current Microbiology, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Strategies for lead distribution in organs of Phragmites australis (Cav.) Trin. ex Steud. (Common reed) subjected to Pb pollution in flood and drought environments - Na Zhang; Jing Chen; Zhiqiang Li; Yujie Shi; Chunsheng Mu; Zhenhua Zhang (Hydrobiologia, 2018)

Rock burst risk in an island longwall coal face by stress field - Guangjian Liu; Zonglong Mu; Jianjun Chen; Jing Yang; Jinglong Cao (Geosciences Journal, 2018)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Characteristics of nitrogen removal and microbial community in biofilm system via combination of pretreated lignocellulosic carriers and various conventional fillers - Jing Zhao; Lijuan Feng; Jincheng Dai; Guangfeng Yang; Jun Mu (Biodegradation, 2017)

Propionate metabolism and diversity of relevant functional genes by in silico analysis and detection in subsurface petroleum reservoirs - Tao Yang; Serge Maurice Mbadinga; Lei Zhou; Shi-Zhong Yang; Jing-Feng Liu; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2017)

Insertion of a solo LTR retrotransposon associates with spur mutations in ‘Red Delicious’ apple (Malus × domestica) - Mengxue Han; Qibao Sun; Junyong Zhou; Huarong Qiu; Jing Guo; Lijuan Lu; Wenlei Mu; Jun Sun (Plant Cell Reports, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Interaction between southern rice black-streaked dwarf virus minor core protein P8 and a rice zinc finger transcription factor - Jing Li; Nian-Jun Cai; Jin Xue; Jian Yang; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

The spatial distribution of threats to plant species with extremely small populations - Chunjing Wang; Jing Zhang; Jizhong Wan; Hong Qu; Xianyun Mu; Zhixiang Zhang (Frontiers of Earth Science, 2017)

Screening, purification, and characterization of a novel organic solvent-tolerant esterase, Lip2, from Monascus purpureus strain M7 - Li-Jing Kang; Zi-Tong Meng; Chen Hu; Yan Zhang; Hai-Lun Guo; Qing Li; Mu Li (Extremophiles, 2017)

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Non-integrating lentiviral vectors based on the minimal S/MAR sequence retain transgene expression in dividing cells - Zhen Xu; Feng Chen; Lingling Zhang; Jing Lu; Peng Xu; Guang Liu; Xuemin Xie; Wenli Mu; Yajun Wang; Depei Liu (Science China Life Sciences, 2016)

Trade-offs between carbon sequestration, soil retention and water yield in the Guanzhong-Tianshui Economic Region of China - Xiaonan Yang; Zixiang Zhou; Jing Li; Xin Fu; Xingmin Mu; Ting Li (Journal of Geographical Sciences, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Molecular characterization of Beclin 1 in rare minnow (Gobiocypris rarus) and its expression after waterborne cadmium exposure - Xiao-Hong Liu; Zhi-Jian Wang; Dong-Ming Chen; Mu-Fei Chen; Xing-Xing Jin; Jing Huang; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Management planning for endangered plant species in priority protected areas - Chun-Jing Wang; Ji-Zhong Wan; Xian-Yun Mu; Zhi-Xiang Zhang (Biodiversity and Conservation, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Characterization of homologous and heterologous interactions between viroplasm proteins P6 and P9-1 of the fijivirus southern rice black-streaked dwarf virus - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Li Xie; Jian-Ping Chen (Archives of Virology, 2015)

LNA-modified isothermal oligonucleotide microarray for differentiating bacilli of similar origin - Jing Yan; Ying Yuan; Runqing Mu; Hong Shang; Yifu Guan (Journal of Biosciences, 2014)

The role of mast cells in ischemia and reperfusion injury - Mu-qing Yang; Yuan-yuan Ma; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

Inhibiting mast cell degranulation by HO-1 affects dendritic cell maturation in vitro - Yuan-yuan Ma; Mu-qing Yang; Chun-feng Wang; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Effect of 1-Octyl-3-methylimidazolium Chloride on Cell Replication and Membrane Permeability of Escherichia coli DH5α - Changqin Jing; Lingmin Mu; Taifang Ren; Bingnan Li; Sujuan Chen; Wenbin Nan (Bulletin of Environmental Contamination and Toxicology, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Genetic diversity of two Tibetan macaque (Macaca thibetana) populations from Guizhou and Yunnan in China based on mitochondrial DNA D-loop sequences - Li-Jing Zhong; Ming-Wang Zhang; Yong-Fang Yao; Qing-Yong Ni; Jun Mu; Chong-Qing Li; Huai-Liang Xu (Genes & Genomics, 2013)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

The sphingosine-1-phosphate receptor agonist FTY720 prevents the development of anti-glomerular basement membrane glomerulonephritis - Manshu Sui; Jin Zhou; Rujuan Xie; Xiaogang Liu; Suhong Mu; Xibei Jia; Jing Ma; Hongchi Wu (Molecular Biology Reports, 2012)

Molecular characterization and NF-κB-regulated transcription of selenoprotein S from the Bama mini-pig - Ningbo Zhang; Wenqian Jing; Jiayue Cheng; Wentao Cui; Yulian Mu; Kui Li; Xingen Lei (Molecular Biology Reports, 2011)

MiR-106a inhibits glioma cell growth by targeting E2F1 independent of p53 status - Guang Yang; Ruyou Zhang; Xiaofeng Chen; Yulong Mu; Jing Ai; Chen Shi; Yaohua Liu; Changbin Shi; Lihua Sun; Nikolai G. Rainov; Hulun Li; Baofeng Yang; et al. (Journal of Molecular Medicine, 2011)

An approach to the study of copepod egg banks based on efficient DNA extraction from individual copepod eggs - Zhi-Huan Xu; Gui-Zhong Wang; Qian Mu; Li-Sheng Wu; Shao-Jing Li (Marine Biology Research, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Molecular characterization and association analysis of porcine PANE1 gene - Honggang Huang; Hong Deng; Yiling Yang; Zhonglin Tang; Shulin Yang; Yulian Mu; Wentao Cui; Jing Yuan; Zhenfang Wu; Kui Li (Molecular Biology Reports, 2010)

Alu tandem sequences inhibit GFP gene expression by triggering chromatin wrapping - Xiu-Fang Wang; Xiaoyan Wang; Jing Liu; Jingjing Feng; Wenli Mu; Xiaojuan Shi; QinQing Yang; Xiaocui Duan; Ying Xie; Zhanjun Lu (Genes & Genomics, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Molecular marker application in sugarcane - Mu-Qing Zhang; Xue-Fang Zheng; Ai-Li Yu; Jing-Sheng Xu; Hui Zhou (Sugar Tech, 2004)

Identification by PCR of receptor-like protein kinases from Arabidopsis flowers - Taku Takahashi; Jing-Hong Mu; Alexander Gasch; Nam-Hai Chua (Plant Molecular Biology, 1998)

Expression of human muscarinic cholinergic receptors in tobacco - Jing-Hong Mu; Nam-Hai Chua; Elliott M. Ross (Plant Molecular Biology, 1997)